2003
DOI: 10.3201/eid0901.020266
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin–ProducingEscherichia coliInfections Associated with Hemolytic Uremic Syndrome, Italy, 1988–2000

Abstract: The mean annual incidence of hemolytic uremic syndrome in persons <15 years of age in Italy from 1988 to 2000 was 0.28 per 100,000 population. Laboratory investigations showed that Shiga toxin–producing Escherichia coli (STEC) infection occurred in 73.1% of patients. STEC O157 was the most common serotype, but a considerable number of cases were from infections by non-O157 STEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
139
2
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(155 citation statements)
references
References 15 publications
(29 reference statements)
5
139
2
7
Order By: Relevance
“…Theoretically, this ability has clear implications for the severity of Stx-mediated disease symptoms, commensurate with an increased number of toxin gene copies and increased toxin load, but previously this had not been directly and unequivocally demonstrated. Different stx genes, associated with different prophages or prophage remnants, are regularly found in combination within a single host (Allison et al, 2003;Bielaszewska et al, 2007;Eklund et al, 2002;Muniesa et al, 2003;Zheng et al, 2008), and virulence profiles comprising two stx2 genes are frequently associated with HUS and bloody diarrhoea (Banatvala et al, 1996;Eklund et al, 2002;Elliott et al, 2001;Tozzi et al, 2003;Woodward et al, 2002). Furthermore, the presence of two stx operons can lead to increased in vitro toxin expression (Bielaszewska et al, 2006;Cornick et al, 2002;Eklund et al, 2002;Muniesa et al, 2003), though this observation is not without exceptions (Serra-Moreno et al, 2008), nor does it necessarily equate to more severe clinical disease (Bielaszewska et al, 2006;Cornick et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this ability has clear implications for the severity of Stx-mediated disease symptoms, commensurate with an increased number of toxin gene copies and increased toxin load, but previously this had not been directly and unequivocally demonstrated. Different stx genes, associated with different prophages or prophage remnants, are regularly found in combination within a single host (Allison et al, 2003;Bielaszewska et al, 2007;Eklund et al, 2002;Muniesa et al, 2003;Zheng et al, 2008), and virulence profiles comprising two stx2 genes are frequently associated with HUS and bloody diarrhoea (Banatvala et al, 1996;Eklund et al, 2002;Elliott et al, 2001;Tozzi et al, 2003;Woodward et al, 2002). Furthermore, the presence of two stx operons can lead to increased in vitro toxin expression (Bielaszewska et al, 2006;Cornick et al, 2002;Eklund et al, 2002;Muniesa et al, 2003), though this observation is not without exceptions (Serra-Moreno et al, 2008), nor does it necessarily equate to more severe clinical disease (Bielaszewska et al, 2006;Cornick et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A small number (,15) of isolates of non-O157 VTEC are identified annually in England and Wales by diagnostic testing in the LGP using a combination of PCR and culture of faeces from cases of haemolytic uraemic syndrome (HUS) and bloody diarrhoea but their true incidence is unknown. In other countries, non-O157 VTEC has been identified as a significant cause of infectious intestinal disease, including HUS (Tozzi et al, 2003;Mellmann et al, 2008), and its incidence has been found to exceed that of VTEC O157. This may reflect both actual prevalence and differences in testing methods.…”
Section: Introductionmentioning
confidence: 99%
“…Such a rapid epidemiological assessment together with a more effective risk communication effort might have been the best strategy for minimizing the public anxiety that accompanied this outbreak and for deciding more appropriate interventions. Unfortunately, this approach was not adopted, mainly due to an insufficient knowledge of the characteristics of STEC outbreaks, which are relatively uncommon in Italy [8,26].…”
Section: Discussionmentioning
confidence: 99%
“…The system involves most Italian paediatric nephrology units, which notify HUS cases and collect samples for laboratory diagnosis of STEC infection, carried out at the ISS. Between 1988 and 2000, the surveillance system has observed 342 cases of HUS, 73 % of which were shown to be associated with STEC infection [8].…”
Section: Introductionmentioning
confidence: 99%